German causal language annotations and lexicon (verbs, nouns, prepositions) (DE) - Rehbein, Ines; Ruppenhofer, Josef (Universität, 2020)
Annotations of causal verbs, nouns and prepositions in context and lexicon file for causal verbs, nouns and prepositions.
Production date: 2019
Kind of data: Archived tab-separated format (tsv)
Gesehen am 31.03.2020
Keywords: Forschungsdaten; Datenbank